Hydrogel micropost-based qPCR for multiplex detection of miRNAs associated with Alzheimer's disease - Choi, Woongsun; Yeom, Sang Yun; Kim, Junsun; Jung, Seungwon; Jung, Seungho; Shim, Tae Soup; Kim, Sang Kyung; Kang, Ji Yoon; Lee, Soo Hyun; Cho, Il Joo; Choi, Jungkyu; Choi, Nakwon (Biosensors and Bioelectronics, 2018)
Quantitative polymerase chain reaction (qPCR) renders profiling of genes of interest less time-consuming and cost-effective. Recently, multiplex profiling of miRNAs has enabled identifying or investigating predominant miRNAs for various diseases such as cancers and neurodegenerative diseases. Conventional multiplex qPCR technologies mostly use colorimetric measurements in solution phase, yet not only suffer from limited multiplexing capacity but also require target-screening processes due to non-specific binding between targets and primers. Here, we present hydrogel micropost-based qPCR for multiplex detection of miRNAs associated with Alzheimer's disease (AD). Our methodology promises two key advantages compared with the conventional solution-based PCR: 1) nearly no non-specific crosstalks between targets and primers, and 2) practically valuable multiplexing by spatial encoding within a single microchamber. Specifically, we immobilized hydrogel microposts (~ 400 µm in diameter) within commercially available polycarbonate PCR chips by multi-step ultraviolet (UV, 365 nm) exposure. We optimized this photoimmobilization for thermal cycles of PCR as well. Acrylated forward primers incorporated in polyethylene glycol diacrylate (PEGDA) posts played a crucial role to confine fluorescent signal of cDNA amplification within the PEGDA hydrogel. To demonstrate the potential of our platform, we successfully verified multiplex detection of five miRNAs, which were reported to be highly correlated with AD, from a complex buffer of human plasma.
Keywords: Alzheimer's disease; miRNA; Multiplex qpcr; Plastic substrates; Polyethylene glycol diacrylate; Alzheimer Disease; Biosensing Techniques; DNA, Complementary; Humans; Hydrogel, Polyethylene Glycol Dimethacrylate; MicroRNAs; Multiplex Polymerase Chain Reaction; Polyethylene Glycols; Alzheimer's disease; Hydrogel micropost; miRNA; Multiplex qPCR; Plastic substrate; Polyethylene glycol diacrylate (PEGDA)